Kajian kualitatif praktik hygiene dan sanitasi pangan jajanan sekolah dalam konteks kejadian keracunan makanan - Tsaltsa Najwa Fitria; Asti Dewi Rahayu Fitrianingsih; Ahdiyatul Fauza; Delita Septia Rosdiana (UHAMKA PRESS, 2026)
Food poisoning remains a public health problem among elementary school–aged children, particularly due to suboptimal hygiene and sanitation practices associated with school snacks. The food poisoning incident at SDN 1 Cimerang underscored the need for qualitative research to understand the practices and perceptions of the actors involved. This study aimed to explore hygiene and sanitation practices related to school snack foods in the context of a food poisoning incident. A qualitative case study approach was employed. Informants were selected purposively and classified as key informants (the school principal), main informants (snack vendors), and supporting informants (students in grades IV–VI), involving a total of 14 informants. Data were collected through in-depth interviews, observations, and documentation, and were thematically analyzed using NVivo 12. The findings indicated that personal hygiene practices among students and snack vendors remain suboptimal. Observational data revealed that all vendors did not use aprons (100%) and lacked standard waste disposal facilities (100%), while some served food in open conditions (57%). In addition, students frequently consumed snacks without washing their hands and tended to purchase snacks outside the school premises. Although supervision and guidance efforts have been undertaken by the school, they have not been optimal due to limitations in written regulations, resources, and cross-sectoral coordination. This study highlights the importance of strengthening school-based hygiene and sanitation practices through clear regulations, continuous education, and the provision of adequate sanitation facilities to prevent food poisoning incidents among school children.